STUDY OF AUTOMATIC CLEANING SYSTEM APPLICATION AT HEAT EXCHANGER IN ORGANIC RANKINE CYCLE GEOTHERMAL POWER PLANT - Fahlevi, Oktasio
Geothermal energy in Indonesia has medium to high enthalpy characteristics. For case study in the field which is located at PLTP Wayang Windu has a brine temperature of 180 ° C and total mass flow rate of 69,12 kg / s. The brine fluid used to heat the working fluid still has a high temperature when it exits the heat exchanger in the pre-heater and evaporator. The limit of the reduction in the preheater output temperature to avoid scaling is141°C, only that temperature is still high and has the potential to heat the working fluid again. Decreasing the brine temperature outside the silica scaling index (SSI) limits silica deposition on the heat exchanger. The alternative to get large thermal energy by preventing silica scaling is by automatic cleaning (ATCS). By reducing the temperature of the pre heater to 87 ° C, the organic fluid that gets heat from brine water is able to generate turbine power of 130 kW with mass flow rate only 2,178 kg/s and heat demand (Qin) of 867 kW and the heat exchanger effectiveness is 78%. The rest of brine could be used for others ORC in parallel system to get more power output. The operation of this automatic cleaning system can be done by reducing the power to a certain extent. The stages of the decline are 130 kW, 126 kW, 122 kW and 118 kW. To obtain the operating time of ATCS, an analysis of costs and benefits is carried out. The results, with a reduction in power up to 122 kW is more feasible because it has the highest NPV and IRR of Rp.2.815.173.905 and 26.77% with ATCS operating time every 38 hours.